From men's violence to an ethic of care: Ecofeminist contributions to green criminology - Burrell, Stephen R. (Journal of criminology, 2025)
Green criminology has made important contributions to criminological inquiry by highlighting the destructive impact of humans on the more-than-human world. However, it often adopts a gender-neutral lens that overlooks the disproportionate role of men and masculinities in perpetrating green harms. This paper places green criminology into critical dialogue with ecofeminism, arguing that harms against the environment and nonhuman animals are inextricably gendered and should be understood as interconnected forms of men's violence. Ecofeminist insights reveal that violence against the more-than-human world is rooted in hierarchical dualisms, whereby humans are placed separate from and above nature, and the masculine is defined as superior to the feminine. This hierarchical logic enables men to view others in detached, instrumental ways and serves to legitimise acts of men's violence. But just as ecofeminism provides green criminologists with a productive framework for understanding men's violence against the environment and nonhuman animals, it also provides a means of moving beyond this violence. It does this by advocating for an ethic of care that unravels hierarchical modes of thinking and promotes more harmonious relationships between humans and the more-than-human world. By building caring, egalitarian relationships with other living beings (and with their own emotional selves), it is harder for men to act in violent, dominating ways towards others, providing the foundation for more sustainable, interdependent ways of being.